2018
DOI: 10.1021/acs.nanolett.8b01241
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional High-Entropy Alloy–Polymer Composite Nanolattices That Overcome the Strength–Recoverability Trade-off

Abstract: Mechanical metamaterials with three-dimensional micro- and nanoarchitectures exhibit unique mechanical properties, such as high specific modulus, specific strength, and energy absorption. However, a conflict exists between strength and recoverability in nearly all the mechanical metamaterials reported recently, in particular the architected micro/nanolattices, which restricts the applications of these materials in energy storage/absorption and mechanical actuation. Here, we demonstrated the fabrication of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 32 publications
1
92
0
Order By: Relevance
“…Lattice based meta-materials, made up of beam elements, have been traditionally classed as either bending or stretching dominated depending on their connectivity 44 . It is notable that recent experimental work has estabilished that some 3 dimensional lightweight nanolattices exhibit density scaling that is inconsistent with these classifications [65][66][67] . Here we have established, through theory and simulation, the existence of a third class of lattice architecture where both bending and stretching energies must be considered.…”
mentioning
confidence: 99%
“…Lattice based meta-materials, made up of beam elements, have been traditionally classed as either bending or stretching dominated depending on their connectivity 44 . It is notable that recent experimental work has estabilished that some 3 dimensional lightweight nanolattices exhibit density scaling that is inconsistent with these classifications [65][66][67] . Here we have established, through theory and simulation, the existence of a third class of lattice architecture where both bending and stretching energies must be considered.…”
mentioning
confidence: 99%
“…The main advantage of TPL is that it has the highest precision of current 3D AM techniques, but its scalability and efficiency limit its industrial applications. TPL has been used to fabricate various nanolattices with the minimum characteristic size of hundreds of nanometers and the overall size varying from hundreds of micrometers to several centimeters.…”
Section: Fabricationmentioning
confidence: 99%
“…In this sense, most previous studies have mainly focused on improving or tuning the mechanical properties by adopting the principles of flaw insensitivity and size‐strengthening effects. Thus, 3D micro‐/nanolattices have achieved unprecedented mechanical properties, including ultralightweights with 99.9% air but ultrahigh stiffnesses, large deformabilities and recoverabilities, and ultrahigh specific strengths that approach the theoretical limits . In parallel, other studies have been devoted to the design and optimization of novel structures.…”
Section: Introductionmentioning
confidence: 99%
“…Authors concluded that the concept of hierarchical design can be applied to create materials of any order which offer high strength to weight ratio, negative poisons ratio, near infinite bulk to shear modulus ratios. However, the unique properties of micro-lattices such as high specific modulus, specific strength and energy absorption are restricted by the strength-recoverability compromise [41]. To overcome this strength-recoverability trade-off, Zhang et al fabricated threedimensional architected nanolattices from composites.…”
Section: Structural Applications Of Micro-lattice Materialsmentioning
confidence: 99%
“…To overcome this strength-recoverability trade-off, Zhang et al fabricated threedimensional architected nanolattices from composites. The polymer nanolattices are fabricated by twophoton lithography and coating of high entropy alloy is performed by magnetron sputtering [41]. Scanning electron microscope images of the compression tests performed on these nanolattices have shown that these nanolattices show a high specific strength and high energy absorption capability per unit volume.…”
Section: Structural Applications Of Micro-lattice Materialsmentioning
confidence: 99%